Mesrine. Killer instinct [videorecording (DVD)] - Richet, Jean-François; Cassel, Vincent, 1966-; France, Cécile de, 1975-; Depardieu, Gérard, 1948-; Mesrine, Jacques, 1936-1979 (Mesrine saga, 2011)
The first of two parts charts the outlaw odyssey of Jacques Mesrine, the legendary French gangster of the 1960s and 1970s who came to be known as French Public Enemy No. 1 and the Man of a Thousand Faces. Infamous for his bravado and outrageously daring prison escapes, Mesrine carried out numerous robberies, kidnappings, and murders in a criminal career that spanned continents until he was shot dead in 1979 by France's notorious anti-gang unit.